Open-Access Publishing - Nedjeljko Frančula; Dražen Tutić (Kartografija i Geoinformacije, 2013)
Nature, one of the most prominent scientific journals dedicated one of its issues to recent changes in scientific publishing (Vol. 495, Issue 7442, 27 March 2013). Its editors stressed that words technology and revolution are closely related when it comes to scientific publishing. In addition, the transformation of research publishing is not as much a revolution than an attrition war in which all sides are buried. The most important change they refer to is the open-access model in which an author or an institution pays in advance for publishing a paper in a journal, and the paper is then available to users on the Internet free of charge. According to preliminary results of a survey conducted among 23 000 scientists by the publisher of Nature, 45% of them believes all papers should be published in open access, but at the same time 22% of them would not allow the use of papers for commercial purposes. Attitudes toward open access vary according to scientific disciplines, leading the editors to conclude the revolution still does not suit everyone.